Neural Prolotherapy in Persistent Post-Surgery Pain: A Case Report - Abdul Muttalib; Nur Surya Wirawan (Journal of Anesthesiology and Clinical Research, 2023)
Introduction: Persistent postoperative pain is a clinical condition of discomfort (pain) and lasts more than 2 months after surgery without other causes, such as chronic infection or pain due to chronic conditions that occurred before surgery. This study aims to describe PPSP management and its outcomes. Case presentation: A woman, 54 years old, a housewife, came to the hospital with complaints of persistent pain from a surgical scar in the abdominal area. The pain has gotten worse in the last 3 months and sometimes feels like it's spreading to the area around the surgical wound. The pain is felt sharp and hot, spreads to the area around it, and is felt when resting, aggravated by activity experienced 5 months ago since the operation to remove the uterus. The patient was diagnosed with persistent post-surgical pain. Neural prolotherapy is performed on patients with PPSP indications. The drugs used are 5% dextrose solution and 2% lidocaine. Injection of 0.5-1 ml of dextrose was carried out in the area along the surgical scar and its surroundings. After the injection, the patient felt that the pain was reduced (numeric rating scale 1/10). Conclusion: Neural prolotherapy can be used in the management of patients with PPSP complaints. Treatment with neural prolotherapy injection using a mixture of D5% solution and lidocaine has a good prognosis for symptom improvement and relatively minimal complications.